Маркетингове забезпечення антикризового управління аграрним підприємством - Багорка, Марія Олександрівна; Bahorka, Mariia; Устік, Т. В.; Ustik, Tetiana; Юрченко, Наталія Іванівна; Yurchenko, Nataliia (Класичний приватний університет, 2022)
В статті проведено дослідження теоретичних підходів антикризового управління, узагальненні причини кризових явищ аграрних підприємств, визначенні основні складові маркетингового забезпечення в системі антикризового управління для уникнення вразливості підприємства щодо кризових явищ та ліквідації їх наслідків. Представлено основні методологічні підходи, завдання та принципи маркетингового забезпечення, пов’язані з пошуком цільових ринків, проведенням маркетингових досліджень, розробкою конкурентного продукту, а також з організацією зворотного зв’язку зі споживачами, активізації попиту на товар. Маркетингове забезпечення аграрного підприємства в системі антикризового управління є необхідним, адже без нього підприємство не зможе нормально функціонувати і використовувати свої ресурси продуктивно та вигідно. The article examines theoretical approaches to crisis management, summarizes the causes of crisis phenomena in agricultural enterprises, defines the main components of marketing support in the crisis management system to avoid the vulnerability of the enterprise to crisis phenomena and eliminate their consequences. The main methodological approaches, tasks and principles of marketing support are presented, related to the search for target markets, conducting marketing research, developing a competitive product, as well as organizing feedback with consumers, activating demand for the product. The marketing support of the enterprise includes a number of operations of a commercial nature, interrelated with the movement of products from the territory of the producer to the territory of the consumer. At the same time, marketing elements make it possible to maintain the optimal level of financial and economic indicators in production activities. Marketing support develops in the process of overcoming contradictions between external conditions and internal capabilities of the enterprise. Marketing support includes a set of marketing elements, which are a kind of system for solving tasks related to the search for target markets, conducting marketing research, developing a competitive product and other elements of the marketing complex, as well as organizing feedback with consumers. Marketing support of an agricultural enterprise in the anti-crisis management system is necessary, because without it the enterprise will not be able to function normally and use its resources productively and profitably. It can be argued that the key priority of the marketing support of the anticrisis management system is: survival, ensuring (supporting) competitiveness, meeting the needs of customers, optimal use of one's strengths to achieve advantages over competitors, etc., and most importantly - stabilization of the activity of all subsystems of the organization, elimination of contradictions of microeconomic elements systems among themselves and with the external environment to restore the balance of the economic system (organization), restore its viability.
Marketing support of the anti-crisis management of an agricultural enterprise
Keywords: антикризове управління; anti-crisis management; аграрні підприємства; agricultural enterprises; антикризовий маркетинг; anti-crisis marketing; маркетингові заходи; marketing activities; маркетингова інформація; marketing information; антикризова програма; anti-crisis program; маркетингова стратегія; marketing strategy